Executive Secretary of UNCCD, Luc Gnacadja speaks about combating desertification - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Luc Gnacadja, Executive Secretary of UNCCD (United Nations Convention to Combat Desertification), speaks about combating desertification Video by Meerim Shakirova, social media reporter